Imaging of cranio-cervical junction traumas. Issue 127 (June 2020) - Izzo, Roberto; Popolizio, Teresa; Balzano, Rosario Francesco; Simeone, Anna; Gasparotti, Roberto; Scarabino, Tommaso; Muto, Mario
Highlights: This article review is about the classification and pathological aspects of upper cervical spine traumas. Biomechanical aspects are investigated. A brief mention on whiplash is also provided. Abstract: The craniocervical junction (CCJ) or upper cervical spine (UCS) has anatomic features and a biomechanics completely different from the other spinal segment of the spine. Several ligaments and muscles control its motion and function and ensure the maximum mobility and the visual and auditory spatial exploration. UCS traumas represent approximately one-third of all cervical spine injuries. Most of UCS traumas results from blows to the head and sudden deceleration of the body. Thanks to the improvement of the Advanced Trauma Life Support protocols dissociative injuries of CCJ have become less lethal onsite. In other less severe but unstable injuries, patients are neurologically intact at presentation, but they may deteriorate during the stay in hospital, with important clinical and medico-legal consequences. Knowing the peculiarities of UCS is fundamental for the early detection of imaging findings that influences the patient management and outcome. The classification of UCS traumas is mechanistic. More than in any other spinal segment, fractures of CCJ bones can occur without generating instability; on the contrary highly unstable injuries may not be associated with bone fractures. An early and correct diagnosis of occipito-cervical instability may prevent secondary neurological injury. The goal of imaging is to identify which patients can benefit of surgical stabilization and prevent secondary neurologic damage. Actual helical multidetector-CT (MDCT) offers high sensitivity and specificity for bone lesions and displacements in cervical spine traumas, but magnetic resonance imaging (MRI) is increasingly being used to evaluate soft tissues and ligaments, and mainly to identify possible spinal cord injury.